1981
DOI: 10.1093/bja/53.6.591
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Etomidate With Emphasis on Regional Myocardial Blood Flow and Performance

Abstract: The effects of 30-min infusions of etomidate 0.03, 0.12 and 0.24 mg kg-1 min-1 on systemic and regional haemodynamic variables and cardiac performance and metabolism were studied in pigs. The drug caused moderate, but dose-dependent, decreases in the cardiac output, arterial pressure and LVdP/dt max. Myocardial wall thickening, measured by echographic analysis, was decreased by the drug. However, heart rate, myocardial blood flow distribution and myocardial metabolism of lactate, glucose and free fatty acids r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Unfortunately, although most intravenous anaesthetic agents will reduce ICP there is always the danger of cardiovascular depression and a fall in MAP which may reduce CPP. Various workers have demonstrated minimal cardiovascular effects when etomidate is used as an induction agent in man [9,11,21 ], although Prakash et al have demonstrated a dose dependent depression of cardiac output, arterial pressure and left ventricular dp/dt max when etomidate infusions were administered to pigs [18]. These effects were relatively minor at a dose equivalent to that required for surgical anaesthesia, but cardiovascular depression might be anticipated in patients given higher doses of etomidate.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, although most intravenous anaesthetic agents will reduce ICP there is always the danger of cardiovascular depression and a fall in MAP which may reduce CPP. Various workers have demonstrated minimal cardiovascular effects when etomidate is used as an induction agent in man [9,11,21 ], although Prakash et al have demonstrated a dose dependent depression of cardiac output, arterial pressure and left ventricular dp/dt max when etomidate infusions were administered to pigs [18]. These effects were relatively minor at a dose equivalent to that required for surgical anaesthesia, but cardiovascular depression might be anticipated in patients given higher doses of etomidate.…”
Section: Discussionmentioning
confidence: 99%